The patron as producer: libraries, web 2.0, and participatory culture - Deodato, Joseph (Journal of documentation, 2014)
Purpose This article offers a theoretical framework for applying Web 2.0 technologies and design principles to the development of participatory cultures within libraries. A participatory culture is one that focuses on facilitating interaction and the creation of content by users rather than the consumption of content created or compiled by experts. Design/methodology/approach This study is a literature-based theoretical analysis that explores the role of libraries as agents of cultural hegemony and techniques for developing socially responsible library praxis. It combines insights from a variety of discourses including Western Marxist theories of hegemony, critical theories of library and information science, professional literature regarding “Library 2.0” service models, and media studies theories of participatory culture. Findings Libraries do not just organize knowledge; they construct it. Furthermore, these constructions tend to reinforce dominant discourses while marginalizing others. By adopting participatory technologies and design principles, libraries can support greater diversity of expression and create spaces for marginalized discourses. Practical implications This article offers suggestions for applying principles of participatory culture to the design of library services such as collection development, cataloging and classification, reference, instruction, and institutional repositories. Originality/value This article provides a conceptual framework for understanding and evaluating the significance of Web 2.0 for LIS by applying theoretical perspectives from other disciplines.